Effect of digital game addiction on healthy lifestyle parameters in young adults - Tanrıverdi, Müberra; Yekelenga, Sultan (Journal of Dependence, 2019)
Objective: In this study, it is aimed to investigate the effect of recently discussed digital game addiction on healthy lifestyle behaviors of young population. The spread and accessibility of digital games through easy portable devices such as tablets, phones and game consoles has raised the question of the risk to a healthy lifestyle. Developing behavior is important for a healthy future and life.Method: The study was conducted with self-study and questionnaires presented at a university with a young population. Digital Game Addiction Scale and Healthy Lifestyle Behavior Scale were used in the application and evaluation of the study.Results: The study consisted of 113 participants (74.3% (n = 84) females and 25.7% (n = 29) males). The mean age of participants were 22.11±0.945 (min-max = 21-24) years, and 80 (70,80%) of with an at ideal weight. No statistically significant correlation was found between the digital game addiction scale and the total score of the healthy lifestyle behavior scale (r = -0.185; p = 0.186).Conclusion: According to the results of the study, it is seen that young people are at risk of addiction to digital games and healthy lifestyle behaviors are affected significantly at these ages. We believe that the education to develop healthy lifestyle behaviors will raise awareness and have positive effects. By gaining awareness of the efficient using and planning of time, the controllability of the time spent with the game will be ensured.
Keywords: Behavior; digital game; healthy life; young adult